Transcription factors-golden keys to modulate the plant metabolism to develop salinity tolerance - Basharat Ahmad Bhat; Rakeeb Ahmad Mir; Wajahat Rashid Mir; Syed Suhail Hamdani; Manzoor Ahmad Mir (Plant Stress, 2024)
Abiotic stressors such as drought, low temperature, heavy metals, waterlogging, nutrient imbalance, and salinity are major factors that affect the growth and development of crop plants, which, in turn, results in severe loss in production and yield of economically important crops. Current literature backs up the effect of high salinity on almost all crop plants. Thus, it can be concluded that salinity stress is amongst the most dominant abiotic stress factors in current farming systems, which counteract achieving the goal of “zero hunger.” Consequently, there is a dire need to improve crop plants to develop salinity tolerance for higher yield and production, even in salinity agricultural habitats. The last few decades have established a mechanistic understanding and have identified the molecular determinants favoring salinity tolerance in crop plants. Stress-responsive transcriptional control is the best strategy crop plants adapt to alleviate abiotic stressors, especially salinity stress. In crop plants, transcription factors (TFs) central to the regulation of salinity tolerance include bZIP, WRKY, NAC, AP2/ERFBP, bZIP, and MYB. Studying these TFs and their molecular mechanisms can facilitate their molecular modification at the genetic level to modify crop plants for stress tolerance. Collectively, these reports suggest that TFs enhance tolerance to salinity stress directly or indirectly through diverse signaling pathways. This review summarizes the recent developments in deciphering the mechanistic regulation of TFs in controlling the cellular process and gene expression under salinity stress. Finally, we highlight the way forward in applying genome editing technologies to modulate TFs as hallmark genes in circumventing salinity stress in crop plants.